Improving Citrus Nitrogen Uptake Efficiency: Effective Irrigation Scheduling - Kelly T. Morgan; Edward A. Hanlon (EDIS)
SL-247, a 13-page illustrated document by K. T. Morgan and E. A. Hanlon, addresses citrus irrigation scheduling and its relationship to both nutrition and fertilizer management. Includes additional resources. Published by the UF Department of Soil and Water Sciences, August 2007.